11 days in August a chronicle of the Aquino assasination - Hermano, Terry Z.; Salvador, Eva G. (Communication Foundation for Asia, 2009)
A documentary that vividly depicts the grief and awakening of the Filipino people from lethargy as a result of the martyrdom of opposition leader and former Senator Benigno S. Aquino on August 21, 1983. It traces the events from the time he arrived at the International airport till the time he was laid to rest by millions of Filipinos.